2016
DOI: 10.1136/bcr-2016-214599
|View full text |Cite
|
Sign up to set email alerts
|

An anterior jugular vein variant in a patient requiring tracheostomy, demonstrating the importance of preoperative/procedural ultrasound

Abstract: A 50-year-old woman was admitted to the intensive care unit (ICU) for a life-threatening exacerbation of asthma requiring intubation and ventilation for 7 days. On day 8, she was stepped down from the ventilator via the insertion of a tracheostomy to aid weaning. It was initially decided that a percutaneous tracheostomy would be attempted on ICU, however, following further consideration, it was decided that due to anatomical factors (short neck) a surgical tracheostomy would be performed by the ear, nose and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10] Neck ultrasonography helps determine the location and characteristics of the AJV and jugular venous arch before a surgical treatment. 2,4,6 In this Korean cadaveric study, no significant difference in anatomical characteristics was found according to gender or AJV variation except for a difference in the length of the neck according to gender. However, through this study, it was possible to find a safety zone at the main landmark of the neck that could avoid AJV damage (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10] Neck ultrasonography helps determine the location and characteristics of the AJV and jugular venous arch before a surgical treatment. 2,4,6 In this Korean cadaveric study, no significant difference in anatomical characteristics was found according to gender or AJV variation except for a difference in the length of the neck according to gender. However, through this study, it was possible to find a safety zone at the main landmark of the neck that could avoid AJV damage (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to avoid AJV damage, surgeons should be fully familiar with anatomical features of the AJV before initiating head and neck surgical procedures. 1–10 Neck ultrasonography helps determine the location and characteristics of the AJV and jugular venous arch before a surgical treatment. 2,4,6…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations